The Anti-proliferative Ability of the Ethanol Extract of Annona muricata Leaves on Widr Cancer Cells - Yoni Astuti; Agus Suharto; Sabtanti Harimurti; Wahyu Joko Priambodo (Universitas Muhammadiyah Yogyakarta, 2022)
Soursop (Annona muricata) leaves are widely distributed in the tropics, including Indonesia. Soursop leaves are known to contain many anticancer compounds. Research from various countries using soursop leaves provides a different picture of the size of the dose. This research is qualitative research to determine the antiproliferative properties of soursop leaf alcohol extract on Widr cells as a model of colon cancer cells. The soursop leaves were provided from Medicinal Plant and Traditional Medicine Research and Development Center inTawangmangu. The thin-layer chromatography method was used to analyze the profile of soursop leaf extract. Microtetrazolium (MTT) proliferation test was used to analyze antiproliferative effects. The result showed that the essence quality of soursop leaves in aquoes solution was (20.65 ±0.07) % ; in ethanol solution was (19.22±0.34 ) %. The profile of ingredient soursop leaves was more visible in 366 than in 254. The ethanol extract of soursop leaves showed an antiproliferation effect at IC 50 at a dose 450 ug/ml. In conclusion, the ethanolic extract of Annona muricata showed antiproliferative properties at a dose of 450 ug/ml and having a half cell dose of IC 50.